EFEK MODERASI KEPEMIMPINAN TRANSFORMASIONAL PADA PENGARUH PERSONALITY TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) - Mahardika, I Wayan Putra; Riana, Gede; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
OCB an extra role shown by a person so as to affect the performance of the organization. The purpose of this study was to determine the relationship between personality with organizational citizenship behavior, and knowing moderation transformational leadership role in the relationship of personality with organizational citizenship behavior (OCB) with Moderated Regression Analysis (MRA). The research instrument used 79 respondents out of 379 employees at the State General Hospital. The results showed that personality has a positive and significant impact on OCB. Furthermore Transformational Leadership has a positive and significant impact on OCB. This indicates that the higher the effect of transformational leadership, the higher OCB owned by employees and employee proficiency level. While in the interaction did not prove transformational leadership role as moderating the relationship between the personality of the OCB. The implication of this research is to serve as a reference in future recruitment.
Keywords: Personality, OCB and Transformational Leadership